Sexuality in Older Adults (65+)—An Overview of the Literature, Part 1: Sexual Function and its Difficulties. Issue 1 (2nd January 2017) - Træen, Bente; Hald, Gert Martin; Graham, Cynthia A.; Enzlin, Paul; Janssen, Erick; Kvalem, Ingela Lundin; Carvalheira, Ana; Štulhofer, Aleksandar
ABSTRACT: Objectives : The aim of the current article was to provide an overview of literature on sexual function and sexual difficulties in older adults. Method : The authors conducted a narrative review of papers published in English between January 2005 and July 2015 based on an extensive search in PsycINFO. Results : The review showed that although common biological changes may adversely affect sexual function in old age, sexual experience seems to also be affected by psychological and interpersonal factors. Conclusions : Greater life expectancy and better medical care will result in older individuals with chronic diseases living longer. The need for help to cope with changes in sexual health is likely to increase in older adults, as sexuality may be negatively affected through several pathways.